Thiol-disulphide homeostasis, ischemia-modified albumin, trace elements and vitamins in vitiligo patients - Esra Firat Oguz; Yildiz Hayran; Çiğdem Yücel; Funda Eren; Murat Kizilgün; Özcan Erel (Wolters Kluwer Medknow Publications, 2023)
Background: Vitiligo, a multifactorial, depigmented skin disease, is characterised by selective loss of functional melanocytes leading to pigment reduction in the affected areas of the skin. Aim: We aimed to examine thiol-disulphide homeostasis, IMA, copper, zinc, selenium, vitamin A and vitamin C levels in vitiligo patients. Materials and Methods: The study included 83 vitiligo patients and 72 healthy controls. Copper, zinc, and selenium levels were measured by atomic absorption spectrophotometer; vitamin A and E levels were measured by high-performance liquid chromatography. Ischemia-modified albumin and native/total thiol levels were measured by colourimetric method. Results: Serum native and total thiol levels were significantly lower in vitiligo patients (P < 0.001, for all). Zn levels were significantly higher in vitiligo patients than in the control group (P = 0.004). There was no statistical difference in terms of Cu, Se, vitamin A and vitamin E levels. Conclusions: All thiol-disulphide homeostasis parameters (the most important antioxidant-oxidant system in circulation), trace elements, and vitamins together were evaluated in the present study in vitiligo patients. It can be concluded that vitiligo patients have increased oxidative stress status, and also the increase in the dissemination of the disease also increases the oxidative stress in the body.